1999
DOI: 10.1046/j.1365-2672.1999.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Low level chemiluminescence from liquid culture media

Abstract: Low level chemiluminescence (CL) can be observed from autoclaved liquid culture media, as used in microbiology. The light emission is oxygen-dependent and arises from reactions following auto-oxidation of reducing Maillard products which are formed during autoclaving. The inhibition of this CL by radical scavengers and antioxidants has been studied. As superoxide radicals and hydrogen peroxide are predominantly involved in the initiation of the CL, the investigation of CL from culture media offers a convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One is the high LDCL background in the disrupted cell solutions, and another is that the amount of SOD required for an efficient quenching of chemiluminescence is relatively high and far above the amount usually required for the scavenging of O 2 и− in a model system, due to competition with a ubiquity of other reaction partners in the medium, which allows O 2 и− to escape dismutation. This latter viewpoint is supported by the work of Vogel and Sussmuth (1999). Accordingly, we examined the effects of addition of inhibitors of Cu,Zn-SOD and Mn-SOD, diethyldithiocarbamate and sodium azide, to the intact pellet suspensions, and observed that this resulted in an increased LDCL.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One is the high LDCL background in the disrupted cell solutions, and another is that the amount of SOD required for an efficient quenching of chemiluminescence is relatively high and far above the amount usually required for the scavenging of O 2 и− in a model system, due to competition with a ubiquity of other reaction partners in the medium, which allows O 2 и− to escape dismutation. This latter viewpoint is supported by the work of Vogel and Sussmuth (1999). Accordingly, we examined the effects of addition of inhibitors of Cu,Zn-SOD and Mn-SOD, diethyldithiocarbamate and sodium azide, to the intact pellet suspensions, and observed that this resulted in an increased LDCL.…”
Section: Discussionmentioning
confidence: 82%
“…Another reason is that the culture medium may quench LDCL of fungal pellets to some extent for a variety of reasons. Regarding this, Vogel and Sussmuth (1999) found that low-level chemiluminescence can be observed from autoclaved liquid culture media, as used in microbiology. The light emission is oxygen-dependent, and O 2 и− and H 2 O 2 are predominantly involved in the initiation of the chemiluminescence.…”
Section: The Effect Of Pellet Pretreatment Upon Ldclmentioning
confidence: 99%